PERAWATAN BAHAN PUSTAKA DI PERPUSTAKAAN - ketut ayu sanjiwani (Journal Social and Humaniora, 2017)
Treatment of library materials is a very important activity, which with good care and true, it is expected that the existing collection last long. Library collections preservation e?orts done by: 1. Clean the storage shelves of books and book by using Vacuum cleaner 2. Put the book on the glass cupboard 3. Installing air conditioning in the room of the library 4. Spraying of insecticides with a glass filter or glass di?user in order to weaken the incoming sunlight Fumigation aimed at killing insects, especially eggs and larvae and can be lethal fungus 7. Laminate is a way to protect the already fragile books that kept, of course, will a?ect the positive image of the quality of library services, users visit the library and take advantage of the school library service facilities. Keywords: Nursing; Library materials; fumigation; laminates